Pakistan : Country Water Resources Assistance Strategy, Water Economy : Running Dry - World Bank (Washington, DC, 2012)
The water economy of Pakistan depends fundamentally on a gigantic and complex hydraulic infrastructure system. There are now a set of related challenges which have to be addressed - how to maintain what has been built, what major new system-wide infrastructure needs to be built, what infrastructure needs to be built for populations who have not been served and for environmental protection, and how to build institutions that will manage the resource effectively in the looming era of scarcity. First is rehabilitation and maintenance. Many elements of the vast hydraulic system are now reaching the end of their design lives, and have to be rebuilt. There is an enormous backlog of deferred maintenance. Second is the urgent need for construction of major new storage on the Indus. Third, there are needs for large investments in meeting the needs of those who do not have water and sanitation services in cities, towns and villages. Fourth, Pakistan has been accumulating an "environmental debt" by not investing in municipal and industrial wastewater. It is clear that this has to change, and that it is going to take large amounts of investments. Fifth and finally, Pakistan has to walk o n two legs - investing simultaneously in infrastructure and in developing the institutions required for the sustainable management of increasingly-scarce water. The resource requirements for all of these priorities are very large. Government faces three essential tasks. First, is to set priorities for the short and medium term. Second, to define the principles which will govern what proportions of the initial and recurrent costs are paid by taxpayers and by users. Third, government has to ensure that the limited financial resources are used very efficiently. This is obviously not happening in the "business-as-usual" model at present. It is going to mean exploring a whole set of mechanisms for introducing competition, for paying for output not inputs, and for increasing accountability.